Pink Tax: As a Form of Gender Identity in International Products? - Diavika Febriyanti; Wisnu Yuwono (Universitas Negeri Gorontalo, 2023)
Knowledge about the existence of this Pink Tax is still very lacking in Indonesia. The Pink Tax weakens women's purchasing power by forcing them to spend more money on their daily needs, this creates unfair gender-based pricing. This study aims to analyze the effect of gender-based pricing, gender discrimination, gendered product marketing, price discrimination, and willingness to pay Pink Tax. This research method uses a primary data approach that is distributed to 263 people respondents, with the SmartPLS tool. The results of this research conclude that gender-based pricing only has an effect on Pink Tax, while gender discrimination, gendered product marketing, price discrimination, and willingness to pay do not have a significant effect on Pink Tax. These results indicate that brands often only take the opportunity to exaggerate women's goods and are considered the norm for women's consumption. It is also stated that gender discrimination is not only manifested in the form of price but can be directed in the form of diversification.